Effect of acoustic excitation toward jet flame: an experimental design - Sapit, Azwan; Razali, Mohd Azahari; Hushim, Mohd Faisal; Khalid, Amir; Mohmad Ja'at, Md Norrizam; Samsubaha, Muhammad Fauzi; Tuan A Talib, Tuan Mohamad Kamarul Hisyam (Penerbit Akademia Baru, 2019)
Direct imaging technique is always used to obtain correlation of flame height or any other parameter of the visible portions of the flame. This is one of the important methods used in the combustion community to determine the characteristic of flame. Recently, the imaging technique has been developed and enhanced to provide more accurate data. However the utilization of the technology, such as the used of laserbased technique and acquiring sensor, increased the complexity of the process and also increased the amount of cost practically. This paper presents the results of an acoustic excitation towards a Liquid petroleum gaseous flame by using the direct visualizing technique. The direct visualizing technique is used to acquire the flame image and the images will be analyzed by using image analysis software. Results show the flame length at the flame core decreases when the amount of acoustic gradually increases. The effect of excitation towards the flame core is being investigated due to its significant influence toward the overall flame characteristic.